# arrow_back If $\underline{a}=(2,1,-1)$ and $\underline{b}=(-1,2,1)$, then $2 \underline{a}-3 \underline{b}$ is equal to

10 views
If $\underline{a}=(2,1,-1)$ and $\underline{b}=(-1,2,1)$, then $2 \underline{a}-3 \underline{b}$ is equal to

A) $(1,-4,-5)$

B) $(7,-4,5)$

C) $(7,-4,-5)$

D) $(7,4,-5)$

E) none of the above

## Related questions

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
If $\vec{a}=(2,1,-1)$ and $\vec{b}=(-1,2,1)$, then $2 \vec{a}-3 \vec{b}$ is equal to
If $\vec{a}=(2,1,-1)$ and $\vec{b}=(-1,2,1)$, then $2 \vec{a}-3 \vec{b}$ is equal toIf $\vec{a}=(2,1,-1)$ and $\vec{b}=(-1,2,1)$, then $2 \vec{a}-3 \vec{b}$ is equal to &nbsp; A) $(1,-4,-5)$ B) $(7,-4,5)$ C) $(7,-4,-5)$ D) $(7,4, ... close 0 answers 12 views close 0 answers 12 views Let$z_{1}=\left|z_{1}\right|\left(\cos \left(\theta_{1}\right)+i \sin \left(\theta_{1}\right)\right)$and$z_{2}=\left|z_{2}\right|\left(\cos \left(\theta_{2}\right)+i \sin \left(\theta_{2}\right)\right)$be two complex numbers.Let$z_{1}=\left|z_{1}\right|\left(\cos \left(\theta_{1}\right)+i \sin \left(\theta_{1}\right)\right)$and$z_{2}=\left|z_{2}\right|\left(\cos \left(\ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
What is the product of $A$, $B$ and $C$?
What is the product of $A$, $B$ and $C$? \text { Given } A=\left\begin{array}{ll} 4 &amp; 5 \end{array}\right, B=\left\begin{array}{llll} 1 &amp; 1 &amp; 2 &amp; 1 \end{ar ...
close
Do the points $A(1,1,1), B(-2,0,3)$, and $C(-3,-1,1)$ form the vertices of a right triangle? Explain.
Do the points $A(1,1,1), B(-2,0,3)$, and $C(-3,-1,1)$ form the vertices of a right triangle? Explain.Do the points $A(1,1,1), B(-2,0,3)$, and $C(-3,-1,1)$ form the vertices of a right triangle? Explain. ...
Let $A$ and $B$ be two square invertible matrices of the same order. Then $\left((A B)^{T}\right)^{-1}$ is equal to
Let $A$ and $B$ be two square invertible matrices of the same order. Then $\left((A B)^{T}\right)^{-1}$ is equal toLet $A$ and $B$ be two square invertible matrices of the same order. Then $\left((A B)^{T}\right)^{-1}$ is equal to &nbsp; A) \$\left(B^{T}\right)^{- ...